Understanding the economic consequences of shifting trends in population health - Pierre-Carl Michaud; Dana Goldman; Darius Lakdawalla; Yuhui Zheng; Adam H. Gailey (Institute for the Study of Labor (IZA), 2009)
The public economic burden of shifting trends in population health remains uncertain. Sustained increases in obesity, diabetes, and other diseases could reduce life expectancy - with a concomitant decrease in the public-sector's annuity burden - but these savings may be offset by worsening functional status, which increases health care spending, reduces labor supply, and increases public assistance. Using a microsimulation approach, we quantify the competing public-finance consequences of shifting trends in population health for medical care costs, labor supply, earnings, wealth, tax revenues, and government expenditures (including Social Security and income assistance). Together, the reduction in smoking and the rise in obesity have increased net public-sector liabilities by 430bn, or approximately 4% of the current debt burden. Larger effects are observed for specific public programs: annual spending is 10% higher in the Medicaid program, and 7% higher for Medicare.
urn:nbn:de:101:1-2009092869
Keywords: I10; I38; J26; 330; Disability; health care costs; social security; microsimulation; Gesundheit; Gesundheitskosten; Öffentlicher Haushalt; Arbeitsangebot; Einkommen; Öffentliche Sozialausgaben; Schätzung; USA